Electrochromic device with controlled infrared reflection
By using a transparent conductive film with a periodic gradient groove structure and a hollow grid-shaped upper electrode layer formed by laser etching in the electrochromic material, combined with a doped oxide layer, the shortcomings of existing electrochromic materials in infrared radiation regulation performance are solved, and the controllable adjustment of infrared reflectivity and emissivity and the improvement of charge transfer efficiency are achieved.
Patent Information
- Application Number
- CN202411164359.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electrochromic materials have shortcomings in infrared radiation regulation performance, and cannot effectively control infrared reflectivity and emissivity.
A transparent conductive film with a periodic gradient groove structure is used as the lower electrode layer, and a hollow grid-shaped upper electrode layer is formed by laser etching. Combining a doped anode discoloration layer of nickel oxide or vanadium oxide, a doped cathode discoloration layer of WOx and a protective layer of protecting layer, a fully solid electrochromic material system is constructed.
Controllable adjustment of infrared reflectivity and emissivity is achieved, which improves charge transfer efficiency and cycle life of electrochromic materials, while avoiding the problems of aging of organic materials and poor infrared transmission performance.
Smart Images

Figure CN119596608A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochromic materials, and in particular relates to an electrochromic device with controlled infrared reflection. Background Art
[0002] Electrochromic infrared radiation is a special type of electrochromic material that is currently widely studied. Electrochromic materials refer to materials that can change their color, visible light transmittance, sunlight transmittance and other properties under the action of an electric field.
[0003] Ordinary float glass absorbs infrared and cannot transmit infrared rays in the range of 5μm-50μm; the commonly used transparent conductive films as electrodes have high infrared reflectivity and low transmittance, and cannot reflect the regulation performance of electrochromic materials on infrared radiation.
[0004] There is an existing technology that discloses a variable emissivity, variable reflectivity electrochromic intelligent thermal control coating and a preparation method. It adopts the method of pre-doping control of conductive polymers and multi-layer composite optoelectronic matching to effectively reduce the electrochromic starting voltage and increase the range of change of the reflectivity and emissivity of the electrochromic active layer; the prepared electrochromic coating is DC driven, the driving voltage is less than 2V, the reflectivity change is greater than 0.4, the emissivity change is greater than 0.25, and it can undergo 100 temperature changes of plus or minus 100 degrees; there is also an existing technology that discloses a visible-infrared compatible stealth device and a preparation method, the device consists of an electrochromic device and a photonic crystal device, and is overall coated and heat-sealed with an outer transparent packaging layer, which can achieve continuous variable color of the entire visible light spectrum and a modulation amplitude of infrared emissivity of about 50%. Another prior art discloses an electrochromic device with controlled infrared reflection, which includes a multilayer stack between a carrier substrate and a counter substrate, the carrier substrate is transparent in the infrared range, and the multilayer stack includes: a metal grid transparent in the infrared range forming a first electrode, an electrochromic functional system, a metal layer capable of reflecting infrared radiation forming a second electrode, and a laminated intermediate layer made of a thermoplastic polymer; the electrochromic functional system combines a viologen material and an electrochromic material so that the absorption can be adjusted within a wider wavelength range than the viologen system, and the reflectivity changes by 10%-15% in the range of 3μm-5μm; ITO glass is used as a counter electrode of the smart dimming glass, and its electrochemical capacity per unit area is usually small. It is generally necessary to increase the electrochemical capacity of the ITO conductive film by increasing the applied voltage, thereby improving the electrochromic efficiency of the smart dimming glass. However, increasing the applied voltage will shorten the cycle life of the electrochromic smart dimming glass. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides an electrochromic device with controlled infrared reflection to solve the existing problems.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: An electrochromic device with controlled infrared reflection comprises a substrate and a lower electrode layer, an anode color-changing layer, an ion transport layer, a cathode color-changing layer, an upper electrode layer and a protective layer sequentially deposited on the substrate; the upper electrode layer is a hollow grid-like, strip-like or ring-like structure, and the lower electrode layer is a structure with periodic grooves; the width L and height H of the grooves are equal, and the grooves are formed by continuously connecting a plurality of quarter concave spherical surfaces with the same radius R and a plurality of half convex spherical surfaces with the same radius R.
[0007] Furthermore, the upper electrode layer is a hollow grid structure, the width of the ITO strip is 0.2-0.3 mm, and blank areas are formed between the ITO strips.
[0008] Furthermore, the radius R of the concave spherical surface is equal to the radius R of the convex spherical surface, and two adjacent quarter concave spherical surfaces are respectively connected to the highest point and the lowest point of the half convex spherical surface.
[0009] Furthermore, the substrate is sapphire or silicon or germanium or zinc sulfide or zinc selenide or cadmium telluride or calcium fluoride, or barium fluoride or magnesium fluoride, or glass transparent to infrared rays, or polyethylene; the protective layer is selected from at least one of nitrides and oxides, with a thickness of 10nm-30nm and an average roughness of 2nm-3nm; the nitride mainly includes silicon nitride or aluminum nitride; the oxide mainly includes niobium oxide, titanium oxide, zirconium oxide or silicon oxide.
[0010] Furthermore, the period length L of the gradient groove is 90-120 nm.
[0011] Furthermore, the spherical radius R is 11.25-15 nm.
[0012] Furthermore, the lower electrode layer is selected from a transparent conductive material; the upper electrode layer is selected from a transparent conductive material or a metal material; the transparent conductive material is selected from at least one of tin oxide doped with fluorine, indium oxide doped with tin and zinc oxide doped with aluminum, with a thickness of 300nm-600nm; and an average roughness of 40nm-50nm; the metal material is selected from at least one of Cu, Au and Pt, with a thickness of 8nm-15nm and an average roughness of 3nm-5nm.
[0013] Furthermore, the anode color-changing layer is doped with nickel oxide or vanadium oxide; the main valence state of nickel in the nickel oxide is +2, followed by +1; the main valence state of vanadium in the vanadium oxide is +5, followed by +4; the thickness of the anode color-changing layer is 300nm-400nm, and the average roughness is 10nm-15nm; the doping element of the chromium oxide or vanadium oxide is selected from at least one of Li, Al, Zr, Y, Si, Sn, Cu, Zn, Ti, Au, Ga, Ge, Cd, Sb, Bi and W, and the doping amount is 5-10% mol.
[0014] Furthermore, the ion transport layer is selected from at least one of oxides, nitrides and lithium compounds, and has a thickness of 300nm-500nm and an average roughness of 2nm-8nm.
[0015] Furthermore, the cathode color-changing layer is doped with WOx, wherein x is greater than 2.98 and less than 3.2; the thickness of the cathode color-changing layer is 300nm-400nm, and the average roughness is 5nm-10nm; the doping element of the WOx is selected from at least one of Al, Zr, Y, Si, Sn, Cu, Zn, Ti, Au, Ga, Ge, Cd, Sb, Bi, Cr and V, and the doping amount is 2-10% mol.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adopts an all-solid-state electrochromic material system, which can avoid the problems of aging of organic materials and poor infrared transmittance.
[0017] 2. The present invention adopts a transparent conductive film as an electrode material, and realizes infrared transmittance through microstructure processing such as laser etching. Ordinary float glass can be used to realize controllable adjustment of the sunshade performance in the sunlight band of 300nm-2500nm and the radiation performance in the infrared band of 2.5μm-50μm, thereby realizing continuous adjustment of visible light transmittance of 5%-80%, a sunshade coefficient of 0.06-0.9, and an emissivity between 0.2-0.8.
[0018] 3. The lower electrode layer can be configured to have a structure with periodic gradient grooves, wherein the width L and height H of the grooves are equal. This configuration is intended to increase the roughness of the electrode surface and reduce the infrared reflectivity, while increasing the contact area with the anode color-changing layer, thereby improving the charge transfer efficiency. In particular, the grooves are configured to have a step-like groove structure, and the step surface is a quarter concave spherical surface or a half convex spherical surface. The grooves are formed by continuously connecting a plurality of quarter concave spherical surfaces with the same radius R and a plurality of half convex spherical surfaces with the same radius R, which can further increase the contact area with the anode color-changing layer, thereby improving the charge transfer efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic structural diagram of an electrochromic device with controlled infrared reflection of the present invention; Figure 2 A schematic cross-sectional view of the microstructure of the lower electrode layer in the electrochromic device with controlled infrared reflection of the present invention; Figure 3 A schematic diagram of a gradient groove of a lower electrode layer in an electrochromic device with controlled infrared reflection according to the present invention; The reference numerals in the drawings of the specification include: 1-substrate; 100-negative pole of power supply; 2-lower electrode layer; 3-anode discoloration layer; 4-ion transport layer; 5-cathode discoloration layer; 6-upper electrode layer; 7-protective layer. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0021] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on this patent; in order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of the actual product; for those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.
[0022] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "inner", "outer", etc. appear, the orientation or position relationship indicated is based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as a limitation on this patent. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0023] In the description of the present invention, unless otherwise clearly specified and limited, if the term "connection" or the like appears to indicate the connection relationship between components, the term should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two components or the interaction relationship between two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0024] Embodiment 1: like Figure 1-3 As shown, the present invention. Specifically, it includes a substrate 1 and a lower electrode layer 2, an anode discoloration layer 3, an ion transport layer 4, a cathode discoloration layer 5, an upper electrode layer 6 and a protective layer 7 deposited on the substrate 1 in sequence; the upper electrode layer 6 is a hollow grid-like, ring-like or strip-like structure, and the upper electrode layer 6 is connected to the negative pole of the power supply; the upper electrode layer 6 is preferably a hollow grid-like structure, which is beneficial to improve its machinability. In addition, the grid-like and strip-like upper electrode layers are mainly suitable for rectangular devices, while the ring-like upper electrode layers are mainly suitable for circular devices. The lower electrode layer 2 can be set to a structure with periodic gradient grooves (see Figure 2 and Figure 3 ), the width L and height H of the groove are equal. This setting is to increase the roughness of the electrode surface and reduce the infrared reflectivity, while increasing the contact area with the anode color-changing layer, thereby improving the charge transfer efficiency. The groove is specially set to a step-like groove structure, and the step surface is a quarter concave spherical surface or a half convex spherical surface. The groove is formed by continuously connecting a plurality of quarter concave spherical surfaces with the same radius R and a plurality of half convex spherical surfaces with the same radius R, which can further increase the contact area with the anode color-changing layer, thereby improving the charge transfer efficiency.
[0025] During specific implementation, the substrate 1 can be selected from float glass, quartz glass or sapphire, preferably float glass, which is a commonly used material with low cost and easy to obtain.
[0026] In specific implementation, the lower electrode layer 2 is selected from a transparent conductive material; the upper electrode layer 6 is selected from a transparent conductive material or a metal material; the transparent conductive material is selected from at least one of tin oxide doped with fluorine, indium oxide doped with tin, and zinc oxide doped with aluminum, with a thickness of 300nm-600nm and an average roughness of 40nm-50nm; the metal material is selected from at least one of Cu, Au, and Pt, with a thickness of 8nm-15nm and an average roughness of 3nm-5nm. Preferably, the lower electrode layer 2 or the upper electrode layer 6 is selected from indium oxide doped with tin (ITO film), with a thickness of 500nm and an average roughness of 50nm, so that after optimization, both good transmittance and conductivity can be satisfied.
[0027] In specific implementation, the anode color-changing layer 3 is doped with nickel oxide or vanadium oxide; the main valence state of nickel in the nickel oxide is +2, followed by +1; the main valence state of vanadium in the vanadium oxide is +5, followed by +4; the thickness of the anode color-changing layer 3 is 300nm-400nm, and the average roughness is 10nm-15nm. The doping element of the nickel oxide or vanadium oxide is selected from at least one of Li, Al, Zr, Y, Si, Sn, Cu, Zn, Ti, Au, Ga, Ge, Cd, Sb, Bi and W, and the doping amount is 5-10% mol; preferably, the anode color-changing layer 3 is nickel oxide, with a valence state of +2, a thickness of 300nm, and an average roughness of 10nm; its nickel oxide is W, and the doping amount is 5% mol, so that better color-changing effect can be obtained after optimization.
[0028] In a specific implementation, the ion transport layer 4 is selected from at least one of oxides, nitrides and lithium compounds, preferably SiO2 or NbO2, with a thickness of 300nm-500nm and an average roughness of 2nm-8nm; more preferably NbO2, with a thickness of 300nm and an average roughness of 2nm. This optimization can obtain higher ion transport efficiency and good optical matching performance.
[0029] In a specific implementation, the cathode discoloration layer 5 is doped with WOx, wherein x is greater than 2.98 and less than 3.2; the thickness of the cathode discoloration layer is 300nm-400nm, and the average roughness is 5nm-10nm. The doping element of the WOx is selected from at least one of Al, Zr, Y, Si, Sn, Cu, Zn, Ti, Au, Ga, Ge, Cd, Sb, Bi, Cr and V, and the doping amount is 2-10% mol; preferably, the cathode discoloration layer 5 is doped with WO3, and the thickness is 300nm, and the average roughness is 5nm. The doping element of the WO3 is Al, and the doping amount is 2% mol. After such optimization, a better discoloration effect can be obtained.
[0030] In a specific implementation, the protective layer 7 is selected from at least one of nitrides and oxides, with a thickness of 10nm-30nm and an average roughness of 2nm-3nm; the nitride mainly includes silicon nitride or aluminum nitride; the oxide mainly includes niobium oxide, titanium oxide, zirconium oxide or silicon oxide; preferably, the protective layer 7 is zirconium oxide, with a thickness of 20nm and an average roughness of 2nm. This optimization can make the device have the best mechanical properties and the smallest optical loss.
[0031] The present invention also provides a method for preparing an electrochromic device with controlled infrared reflection, comprising the following steps: A lower electrode layer 2, an anode color-changing layer 3, an ion transport layer 4, a cathode color-changing layer 5, an upper electrode layer 6 and a protective layer 7 are sequentially deposited on a substrate 1 by at least sputtering or evaporation to obtain the electrochromic device with controlled infrared reflection; and laser etching and scribing are also performed on the upper electrode layer 6 to form a hollow grid, strip or ring structure.
[0032] In a specific implementation, laser etching and scribing can be performed on the lower electrode layer 2 to form a structure with periodic gradient grooves.
[0033] In specific implementation, the method for preparing the electrochromic device with controlled infrared reflection specifically comprises the following steps: The glass is first cleaned by roller brush and disk brush using deionized water with conductivity less than 10μs / cm at a spray gun pressure of 1-2Kg / cm2, and then ultrasonically cleaned for 20-30min (preferably 30min), and then the surface is dehydrated and air-dried using a high-pressure centrifugal hair dryer, and then placed in a heating chamber for hot air drying (temperature 100-150°C, preferably 150°C) for 10min. After the above parameters are optimized, a clean substrate can be obtained; The lower electrode layer is an ITO film, which is formed by a magnetron sputtering process or an ion beam sputtering process, with the following specific parameters: vacuuming to 3*10-6Torr, power 5-6kW, working gas pressure 2-3mTorr, Ar80-100sccm, O2 5-10sccm, coating temperature 300-350°C, and coating after 30-40min of heat preservation. The coating thickness is 300nm-600nm, preferably 400nm, the surface resistance is 5-6Ω, preferably 5.5Ω, and the average roughness is 40-50nm, preferably 50nm. The above parameters are optimized to improve the conductivity and optical properties of the lower electrode layer. Laser etching and scribing of the lower electrode layer, the complete ITO coated glass is etched into the following shapes along one dimension by laser. Figure 2 and Figure 3The structure of the periodic gradient groove shown in the figure increases the surface roughness of the electrode and reduces the infrared reflectivity, while increasing the contact area with the anode color-changing layer, thereby improving the charge transfer efficiency; the laser etching and scribing adopts an infrared nanosecond laser with a power of 30-60W, preferably 40W (making the electrode surface rougher and the infrared reflectivity lower), and the edge straightness of the clean edge is ±20μm / m. The period length L of the gradient groove is 90-120nm, the spherical radius R is 11.25-15nm, and the groove is formed by connecting a plurality of quarter concave spherical surfaces with the same radius R and a plurality of half convex spherical surfaces with the same radius R; the radius R of the concave spherical surface is equal to the radius R of the convex spherical surface, and two adjacent quarter concave spherical surfaces are respectively connected to the highest point and the lowest point of the half convex spherical surface. After the above parameters are optimized, the conductivity and optical comprehensive performance of the lower electrode layer can be better.
[0034] The anode color-changing layer is a NiLiO film, which is produced by a magnetron sputtering process or an ion beam sputtering process, and uses a NiLi alloy (containing 5-10 mol% Li) target material. The specific parameters are: vacuum to 3*10-6torr, power 6kW, working gas pressure 5mTorr, Ar100sccm, O2 25sccm, coating temperature 150-200°C, preferably 180°C, and coating starts after keeping warm for 30-40min. The coating thickness is 300m-400nm, preferably 400nm, and the average roughness is 5-10nm, preferably 10nm; after coating, keep warm at a temperature of 180-200°C (preferably 180°C) for 30-40min (preferably 30min) and then cool naturally; after optimizing the above parameters, a better color-changing effect can be obtained.
[0035] The ion transport layer can be SiO2 or NbO2 film, using magnetron sputtering process or ion beam sputtering process, the specific parameters are: SiO2 film, Si:Al alloy target (containing 10wt% Al), power 5kW, working gas pressure 3mTorr, Ar120sccm, O2 50sccm, thickness of 200nm-300nm, preferably 300nm; NbO2 film, metal Nb target, power 4kW, working gas pressure 3mtorr, Ar100sccm, O2 40sccm, coating thickness of 300nm-500nm, preferably 300nm, so that the best color change range can be guaranteed after optimization; SiO2 and NbO2 films have the same ion conduction function, SiO2 film process has good repeatability and low cost; NbO2 is preferred, which has good optical matching performance.
[0036] The cathode color-changing layer is a WO3 film, which is produced by magnetron sputtering or ion beam sputtering, and uses a metal W target. The specific parameters are: vacuum to 3*10-6torr, sputtering power 3-5KW, working pressure 3mtorr, Ar 30-50sccm, O2 30-50sccm, coating temperature 300-400℃, preferably 380℃, and coating starts after 30-40min (preferably 30min) of heat preservation. The coating thickness is 300nm-400nm, preferably 300nm, and the average roughness is 5-10nm, preferably 5nm; after coating, the temperature is kept at 300-400℃ (preferably 380℃) for 30-40min (preferably 30min) and then cooled naturally. After the above parameters are optimized, a better color-changing effect can be obtained.
[0037] The upper electrode layer is an ITO film, which is formed by a magnetron sputtering process or an ion beam sputtering process, with the following specific parameters: vacuuming to 3*10-6torr, power 5-8kW, working gas pressure 3mtor, Ar100sccm, O210sccm, coating temperature 300-400°C, preferably 350°C, and coating starts after keeping warm for 30-40min (preferably 30min). The coating thickness is 300nm-600nm, preferably 600nm, the surface resistance is 5-6Ω, preferably 5Ω, and the average roughness is 5-15nm, preferably 10nm; after coating, the film is naturally cooled in a vacuum chamber and then taken out; after the above parameters are optimized, the conductivity and optical comprehensive performance of the upper electrode layer can be better.
[0038] Laser etching and scribing of the upper electrode layer uses an infrared nanosecond laser with a power of 20W and a straightness of ±20μm / m for the edge of the cleaned edge. The complete electrode ITO film surface is etched into a hollow grid, strip or ring structure in two dimensions by laser (in order to transmit infrared rays and reduce the infrared reflection of the electrode itself). Preferably, it is a hollow grid structure. The width of the ITO strip 9 is 0.2-0.3mm, preferably 0.25mm. A blank area 8 is formed between the ITO strips 9. The spacing of the ITO strips 9 has a significant effect on the infrared transmittance performance. When the spacing is 0.75mm, the average transmittance can reach 60%, and when the spacing is 0.25mm, the average transmittance reaches about 25%. To ensure the efficiency of charge transfer, the spacing is controlled at 0.7-1mm, preferably 0.75mm.
[0039] The protective layer is a ZrO2 or Si3N4 film, and a magnetron sputtering process or an ion beam sputtering process is used. The ZrO2 film uses a metal Zr target material. The specific parameters of the sputtering ZrO2 film are: power 5kW, working pressure 3mTorr, Ar 120sccm, O280sccm, thickness 10nm-30nm, preferably 20nm; the specific parameters of the sputtering Si3N4 film are: power 4-8kW, working pressure 3mtorr, Ar 100sccm, N2 40-50sccm, thickness 10nm-30nm, preferably 25nm; ZrO2 film has better scratch resistance and higher light transmittance than Si3N4 film, so ZrO2 film is preferred. After such optimization, the mechanical properties of the device can be the best and the optical loss is small.
[0040] After the above coating is completed, the upper and lower electrode layers are connected to a power source and can be used separately in thermal control, infrared camouflage and other fields; they can also be processed into a hollow structure to make an electrotropic infrared radiation hollow energy-saving window.
[0041] The functions and interaction mechanisms of the above layers are as follows: Upper and lower electrode layers: Indium tin oxide (ITO) film is an n-type semiconductor oxide film that achieves conductivity through the movement of its oxygen vacancies. The ITO film is connected to the external electric field to provide the voltage required for the reaction, and after laser etching, it can diffusely reflect and transmit infrared bands.
[0042] Anode color-changing layer: NiLiO film undergoes redox reaction under the action of electric field, providing Li ions required for color change. Li ions reach the cathode color-changing layer through the ion transport layer.
[0043] Cathode color-changing layer: The WO3 film undergoes an oxidation-reduction reaction under the action of an electric field and combines with lithium ions to form LiWO3.
[0044] Ion transport layer: SiO2 or NbO2 film has higher ionic conductivity and lower electronic conductivity, achieving the function of passing ions and blocking electrons.
[0045] Protective layer: ZrO2 or Si3N4 film isolates external water vapor, resists external friction, and avoids device damage.
[0046] The above are only embodiments of the present invention, and the circuits, electronic components and modules involved are all prior art, which can be fully implemented by those skilled in the art. It is needless to say that the content protected by this application does not involve improvements to software and methods. The common sense such as the known specific structures and characteristics in the scheme is not described in detail here. Ordinary technicians in the relevant field know all the common technical knowledge in the technical field of the invention before the application date or priority date, can obtain all the prior art in the field, and have the ability to apply conventional experimental means before that date. Ordinary technicians in the relevant field can improve and implement this scheme in combination with their own abilities under the enlightenment given by this application. Some typical known structures or known methods should not become obstacles for ordinary technicians in the relevant field to implement this application. It should be pointed out that for those skilled in the art, without departing from the structure of the present invention, several deformations and improvements can be made, which should also be regarded as the scope of protection of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. An electrochromic device with controlled infrared reflection, comprising a substrate and a lower electrode layer, an anode discoloration layer, an ion transport layer, a cathode discoloration layer, an upper electrode layer and a protective layer sequentially deposited on the substrate; the upper electrode layer is a hollow grid, strip or ring structure, characterized in that: The lower electrode layer has a periodic groove structure; the width L and height H of the groove are equal, and the groove is formed by connecting a plurality of quarter concave spherical surfaces with the same radius R and a plurality of half convex spherical surfaces with the same radius R in a continuous manner.
2. The electrochromic device with controlled infrared reflection according to claim 1, characterized in that: The upper electrode layer is a hollow grid structure, the width of the ITO strip is 0.2-0.3 mm, and blank areas are formed between the ITO strips.
3. The electrochromic device with controlled infrared reflection according to claim 1, characterized in that: The radius R of the concave spherical surface is equal to the radius R of the convex spherical surface, and two adjacent quarter concave spherical surfaces are respectively connected to the highest point and the lowest point of the half convex spherical surface.
4. The electrochromic device with controlled infrared reflection as claimed in claim 2, characterized in that: The substrate is sapphire or silicon or germanium or zinc sulfide or zinc selenide or cadmium telluride or calcium fluoride, or barium fluoride or magnesium fluoride, or glass transparent to infrared rays, or polyethylene; the protective layer is selected from at least one of nitrides and oxides, with a thickness of 10nm-30nm and an average roughness of 2nm-3nm; the nitride mainly includes silicon nitride or aluminum nitride; the oxide mainly includes niobium oxide, titanium oxide, zirconium oxide or silicon oxide.
5. The electrochromic device with controlled infrared reflection according to claim 1, characterized in that: The period length L of the gradient groove is 90-120 nm.
6. The electrochromic device with controlled infrared reflection according to claim 1, characterized in that: The spherical radius R is 11.25-15 nm.
7. The electrochromic device with controlled infrared reflection according to claim 1, characterized in that: The lower electrode layer is selected from a transparent conductive material; the upper electrode layer is selected from a transparent conductive material or a metal material; the transparent conductive material is selected from at least one of tin oxide doped with fluorine, indium oxide doped with tin and zinc oxide doped with aluminum, with a thickness of 300nm-600nm and an average roughness of 40nm-50nm; the metal material is selected from at least one of Cu, Au and Pt, with a thickness of 8nm-15nm and an average roughness of 3nm-5nm.
8. The electrochromic device with controlled infrared reflection according to claim 1, characterized in that: The anode color-changing layer is doped with nickel oxide or vanadium oxide; the main valence state of nickel in the nickel oxide is +2, followed by +1; the main valence state of vanadium in the vanadium oxide is +5, followed by +4; the thickness of the anode color-changing layer is 300nm-400nm, and the average roughness is 10nm-15nm; the doping element of the chromium oxide or vanadium oxide is selected from at least one of Li, Al, Zr, Y, Si, Sn, Cu, Zn, Ti, Au, Ga, Ge, Cd, Sb, Bi and W, and the doping amount is 5-10% mol.
9. The electrochromic device with controlled infrared reflection according to claim 1, characterized in that: The ion transport layer is selected from at least one of oxides, nitrides and lithium compounds, has a thickness of 300nm-500nm and an average roughness of 2nm-8nm.
10. The electrochromic device with controlled infrared reflection according to claim 1, characterized in that: The cathode color-changing layer is doped with WOx, wherein x is greater than 2.98 and less than 3.2; the thickness of the cathode color-changing layer is 300nm-400nm, and the average roughness is 5nm-10nm; the doping element of the WOx is selected from at least one of Al, Zr, Y, Si, Sn, Cu, Zn, Ti, Au, Ga, Ge, Cd, Sb, Bi, Cr and V, and the doping amount is 2-10% mol.
Citation Information
Patent Citations
Electrochromic devices and methods for forming such devices
CN106662786A
Electrochromic infrared radiation device and preparation method and application thereof
CN112068378A
Electrochromic intelligent energy-saving window and control system thereof
CN119356003A
Electrochromic device
JP2016114916A
Cited By
Electrochromic intelligent energy-saving window and control system thereof
CN119356003A